Bidding strategies for excess heat producers participating in a local wholesale heat market - Borna Doračić; Matija Pavičević; Tomislav Pukšec; Neven Duić (Energy Reports, 2022)
The heating sector of the European Union covers 80% of the household’s final energy consumption, which shows its relevance for the energy transition to the carbon neutral society, as set out in the Green Deal. Since most of the heat demand is located in the high heat density areas, district heating shows to be a promising solution for reducing the environmental impact of this sector, as it enables the utilisation of renewable energy sources and the use of high efficiency production technologies. An especially interesting source for district heating is excess heat from various industries and tertiary sector buildings, which has a significant technical potential. However, to enable excess heat producers to supply their heat to district heating, third-party access needs to be granted, which calls for a deregulated heat market.This work consists of analysing two different bidding strategies which can be applied on the heat market: total cost and marginal cost biding. The focus here is to research the feasibility of the excess heat sources when different bidding strategies are used, especially when low temperature excess heat is considered, which has variable hourly costs due to the electricity demand for operating a heat pump. The results show that, despite the increased capacity factor of low temperature excess heat when marginal cost biding is used, it remains infeasible when supplying heat to the high temperature district heating networks through a heat market. Therefore, lower temperature district heating is a necessity for a feasible utilisation of low temperature excess heat. Finally, the effect of the power market prices on the low temperature excess heat feasibility was analysed and it was shown that it is significant, which led to the conclusion that introducing a higher share of renewables into the power market could foster the utilisation of these heat sources.